Konsepsi Abdu Al-Samad Al-Jawi Al-Palimbani tentang Akidah Dalam Kitabnya Hidayatul Al-Salikin - nfn. Mujib (Balai Arkeologi Yogyakarta, 1994)
This paper will describe the concepts of faith (Akidah) based on a study of two religious books (1) Hidayatu al-Salokin, the translation of Al-Palimbani from Al-Ghazali religious book of (2) Bidayatu Al-Hidayah. This paper is intended to explain the characterization of Al-Palimbani as a theologian and translator as well as his bold concepts and perspectives on the Islamic Akidah, revealing the background of the book writing so that the problems are clear, in addition to other interesting studies.